(untitled) (Management Dynamics, 2023)
This study examines the relationship between mindfulness practices and strategic decision-making among ethical leaders in human resource management. A positivist, quantitative method is used to assess the influence of techniques such as mindful breathing, mindful technology usage, 3-minute breathing space, mental gym, and daily journaling on strategic decisions (vision formulation, plan design, and execution). Purposive sampling was used to acquire data from 235 Human Resource managers and assistants using a standardized questionnaire. Correlation coefficients reveal strong beneficial links between mindful activities and strategic choices. Regression research reveals substantial positive connections for mindful breathing, 3-minute breathing space, and daily writing, suggesting that frequent participation corresponds with more favorable strategic decision-making. Notably, no statistically significant connections were identified for mindful technology usage, mental gyms, or apps. This study adds vital insights into the relationship between mindfulness practices, especially mindful breathing, 3-minute breathing space, and daily journaling, and ethical leaders’ ability to make smart and strategic decisions in human resource management. The findings provide a more in-depth view of the function of mindfulness in determining strategic choices, expanding knowledge of ethical leadership dynamics in the corporate setting.